2022
DOI: 10.3389/fped.2022.956136
|View full text |Cite
|
Sign up to set email alerts
|

Real-life vaccination coverage in Slovak children with rheumatic diseases

Abstract: BackgroundEvidence-based recommendations for vaccination of patients with pediatric rheumatic diseases (PRDs) are available, their implementation in practice is unknown.ObjectivesTo analyze real-life vaccination coverage in children with PRDs and identify reasons for incomplete vaccination.MethodsUp-to-date information on vaccination status of Slovak children followed at a tertiary pediatric rheumatology center was retrieved from pediatricians over an 18-month period and compared to the standard Slovak Immuniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The risk of infections, missing treatment, disease flare, and non-achievement of the remission usually are not mentioned as factors, associated with incomplete vaccination. Incomplete vaccination in JIA and pediatric rheumatic disease patients were reported in several previous studies[ 18 , 19 , 30 , 31 , 32 ]. From the medical point of view, the main predictors of incomplete vaccination were polyarticular and systemic JIA categories and immunosuppressive medications[ 30 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The risk of infections, missing treatment, disease flare, and non-achievement of the remission usually are not mentioned as factors, associated with incomplete vaccination. Incomplete vaccination in JIA and pediatric rheumatic disease patients were reported in several previous studies[ 18 , 19 , 30 , 31 , 32 ]. From the medical point of view, the main predictors of incomplete vaccination were polyarticular and systemic JIA categories and immunosuppressive medications[ 30 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 78%
“…From the medical point of view, the main predictors of incomplete vaccination were polyarticular and systemic JIA categories and immunosuppressive medications[ 30 , 31 , 33 ]. In our previous study, the younger JIA onset age was associated with a higher proportion of omitted vaccines similar to the study of Minden et al [ 18 ], but some authors reported that preschool children had a similar rate of vaccine coverage as healthy peers[ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations